Geopolymer composition, geopolymer hardened body, and method for producing geopolymer hardened body

By using sodium orthosilicate or anhydrous sodium metasilicate as active agents, avoiding overalkaline solutions, the safety and quality problems in the production of geopolymer hardeners are solved, and safer and more efficient hardener production is achieved. Excellent mechanical characteristics.

CN119137084APending Publication Date: 2024-12-13OSAKA SANGYO UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037289.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2023-05-01
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art requires the use of high alkaline solutions when producing geopolymer hardened bodies, which leads to risk of operation and poor quality. The high alkaline solutions have high deliquesity and make it difficult to pre-store powdered alkaline premixes.

Method used

Sodium orthosilicate or anhydrous sodium metasilicate is used as the active agent to generate sodium hydroxide by reacting with water, avoiding the use of overalkaline solutions, and obtaining excellent results by adjusting the mixing ratio of sodium silicate and adding water. hardener properties.

Benefits of technology

It reduces safety risks in operation, simplifies adjustments at the work site, reduces the possibility of metrology errors, and achieves shorter settling time and high compression strength at room temperature, improving the practicality of the hardened body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137084A_ABST
    Figure CN119137084A_ABST
Patent Text Reader

Abstract

The geopolymer composition comprises: an active filler at least containing blast furnace slag micropowder; and sodium silicate as an active agent. The sodium silicate is sodium orthosilicate or anhydrous sodium metasilicate. If the sodium silicate is sodium orthosilicate, the content of the sodium orthosilicate is 2-50 parts by weight per 100 parts by weight of the active filler. If the sodium silicate is anhydrous sodium metasilicate, the content of anhydrous sodium metasilicate is 10-30 parts by weight per 100 parts by weight of the active filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a geopolymer composition, a hardened body obtained from the composition and a method for producing the hardened body. Background Art

[0002] Geopolymers are attracting attention worldwide as new binders that can replace Portland cement. In Japan, fly ash and blast furnace slag powder are often mixed as the main raw materials for geopolymers.

[0003] The CO2 emissions of geopolymers vary depending on the evaluation method, but when fly ash is used as the main raw material, it is said to have a CO2 reduction effect of about 80% compared to Portland cement. In addition, even when fly ash and blast furnace slag powder are used together, it is said to have a CO2 reduction effect of 65% to 70%.

[0004] Geopolymers are more acid-resistant and heat-resistant (fire-resistant) than hardened Portland cement. Geopolymers are also less susceptible to alkali-silica reactions, and their ability to fix harmful substances such as radioactive materials has been discovered based on their curing mechanism, so their effective use is expected.

[0005] As a prior art related to the present application, Patent Document 1 can be cited. Patent Document 1 discloses a technique for obtaining a hardened body from a geopolymer composition containing active fillers such as fly ash, blast furnace slag, and sewage incineration sludge, and water glass as an alkali activator. This prior art document states that a high-strength hardened body can be obtained by using sodium metasilicate powder as water glass.

[0006] Patent Document 2 discloses a geopolymer composition containing calcium aluminates as a hardening accelerator. Patent Document 3 discloses a geopolymer composition in which the volume ratio of blast furnace slag fine powder to a mixed powder of blast furnace slag fine powder and fly ash is adjusted to 35% to 80%.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-239446

[0010] Patent Document 2: Japanese Patent Application Publication No. 2018-087139

[0011] Patent Document 3: Japanese Patent Application Publication No. 2021-066613 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, in Patent Documents 1 to 3, highly alkaline solutions such as potassium hydroxide solution and sodium hydroxide solution are used to obtain a hardened body. Therefore, in order to protect the body of the operator from the dangers of alkali burns and blindness, it is necessary to pay full attention to the operation during the operation. In addition, when adjusting the work site, if the operator makes an error in the measurement of the highly alkaline solution, there is also the problem that the hardened body is prone to poor quality. In this regard, if all raw materials except water are powdered, premixed and bagged, the adjustment of the work site can be simplified, thereby suppressing the occurrence of measurement errors, etc. However, the deliquescent nature of alkali is high, so it is impossible to pre-store a premix containing powdered alkali in reality.

[0014] An object of the present invention is to provide a geopolymer composition and a technology related thereto which has few operational restrictions and can simplify the adjustment work of a hardened body at a work site.

[0015] Means for solving problems

[0016] Sodium silicate is also called water glass. Most of the compounds collectively called water glass are in liquid form, and only sodium metasilicate and sodium orthosilicate are in powder form. The present inventors conducted research focusing on sodium orthosilicate and anhydrous sodium metasilicate among the powdered sodium silicates. As a result, they accidentally discovered that if these sodium silicates are used, the condensation reaction of the geopolymer will proceed even in the absence of a high alkaline solution.

[0017] Sodium orthosilicate reacts with water to generate sodium metasilicate and sodium hydroxide. Therefore, if sodium orthosilicate is used as an activator, it is not necessary to add a high alkaline solution in order to obtain a hardened body. In addition, anhydrous sodium metasilicate reacts with water to generate water glass and sodium hydroxide. Therefore, similar to sodium orthosilicate, if anhydrous sodium metasilicate is used as an activator, it is not necessary to add a high alkaline solution.

[0018] Therefore, the present inventors have further conducted studies and, as a result, have found that by adjusting the blending ratio of these sodium silicates to an appropriate range, a hardened body obtained by adding water is extremely excellent in practical use, thereby completing the present invention.

[0019] The first invention is a geopolymer composition having the following characteristics.

[0020] The geopolymer composition comprises: an active filler containing at least blast furnace slag powder; and sodium silicate as an active agent.

[0021] The sodium silicate is orthosodium silicate or anhydrous sodium metasilicate.

[0022] When the sodium silicate is sodium orthosilicate, the content of the sodium orthosilicate is 2 parts by weight to 50 parts by weight based on 100 parts by weight of the active filler.

[0023] When the sodium silicate is anhydrous sodium metasilicate, the content of the anhydrous sodium metasilicate is 10 parts by weight to 30 parts by weight based on 100 parts by weight of the active filler.

[0024] The second invention is the same as the first invention, and further has the following features.

[0025] The lower limit of the content of the sodium orthosilicate is 5 parts by weight.

[0026] The third invention is the same as the first or second invention, and further has the following features.

[0027] The upper limit of the content of the sodium orthosilicate is 45 parts by weight.

[0028] The fourth invention is the same as any one of the first to third inventions, and further has the following features.

[0029] The lower limit of the content of the anhydrous sodium metasilicate is 15 parts by weight.

[0030] The fifth invention is the same as any one of the first to third inventions, and further has the following features.

[0031] The upper limit of the content of the anhydrous sodium metasilicate is 25 parts by weight.

[0032] The sixth invention is the same as any one of the first to fifth inventions, and further has the following features.

[0033] The blast furnace slag powder contains a specific surface area of ​​3000cm 2 / g~4000cm 2 The standard surface area of ​​powder and Blaine surface area range is 6000cm / g 2 / g~10000cm 2 / g of high surface area powder.

[0034] The seventh invention is the same as any one of the first to sixth inventions, and further has the following features.

[0035] The above active filler also contains pozzolanic substances.

[0036] The eighth invention is a geopolymer hardened body having the following characteristics.

[0037] The geopolymer hardened body comprises: an active filler containing at least blast furnace slag powder; sodium silicate as an active agent; and water as a hardening agent.

[0038] The sodium silicate is orthosodium silicate or anhydrous sodium metasilicate.

[0039] When the sodium silicate is sodium orthosilicate, the content of the sodium orthosilicate is 2 parts by weight to 50 parts by weight based on 100 parts by weight of the active filler.

[0040] When the sodium silicate is anhydrous sodium metasilicate, the content of the anhydrous sodium metasilicate is 10 parts by weight to 30 parts by weight based on 100 parts by weight of the active filler.

[0041] The ninth invention is a method for producing a geopolymer hardened body having the following characteristics.

[0042] The manufacturing method comprises:

[0043] A process of adding water to a geopolymer composition and kneading the geopolymer composition, the geopolymer composition comprising an active filler containing at least blast furnace slag powder and sodium silicate as an active agent; and

[0044] A step of curing the kneaded product obtained through the above kneading step at room temperature for 3 hours or more.

[0045] The sodium silicate is orthosodium silicate or anhydrous sodium metasilicate.

[0046] When the sodium silicate is sodium orthosilicate, the content of the sodium orthosilicate is 2 parts by weight to 50 parts by weight based on 100 parts by weight of the active filler.

[0047] When the sodium silicate is anhydrous sodium metasilicate, the content of the anhydrous sodium metasilicate is 10 parts by weight to 30 parts by weight based on 100 parts by weight of the active filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 : is a diagram showing the reaction formula of sodium orthosilicate and water.

[0049] Figure 2 It is a diagram showing the reaction formula of anhydrous sodium metasilicate and water.

[0050] Figure 3 This is a flow chart showing an example of a method for producing a geopolymer cured body. DETAILED DESCRIPTION

[0051] The following is a detailed description of the embodiments of the present invention. It should be noted that in this specification, "parts by weight" refers to the ratio relative to the weight of the active filler when the weight is used as the reference. In addition, when "to" is used to indicate a numerical range, the range includes both ends of the numerical value.

[0052] 1. Geopolymer compositions

[0053] The geopolymer composition of the embodiment includes: an active filler containing at least blast furnace slag powder; and sodium silicate as an active agent.

[0054] 1-1. Active filler

[0055] Blast furnace slag powder (hereinafter also referred to as "BFS") used in active fillers is a byproduct obtained when purifying iron in a blast furnace. The main components of BFS are calcium oxide (CaO), silicon dioxide (SiO2), aluminum oxide (Al2O3), etc., and its quality is specified by JIS A6206. BFS is an amorphous material with latent hydraulic properties. The calcium component contained in BFS reacts in the geopolymer composition to form calcium silicate hydrate (CSH) and harden.

[0056] BFS is classified based on the range of Blaine surface area. The range of Blaine surface area is 2750 cm 2 / g and less than 3500cm 2 / g、3500cm 2 / g and less than 5000cm 2 / g、5000cm 2 / g and less than 7000cm 2 / g, and 7000cm 2 / g or more and less than 10000cm 2 / g. As BFS preferably used as an active filler, there is a BFS having a Blaine surface area of ​​3000 cm 2 / g~4500cm 2 / g standard surface area powder and Blaine specific surface area of ​​6000cm 2 / g~10000cm 2 / g of high surface area powder. These BFS are used alone or in combination.

[0057] The active filler "at least contains BFS" means that the geopolymer composition of the embodiment may also contain active fillers other than BFS. As such an active filler, volcanic ash substances can be exemplified. In this specification, volcanic ash substances are substances other than BFS, and are a general term for substances that react with the calcium component contained therein to generate calcium silicate hydrate. Examples of volcanic ash substances include fly ash, metakaolin, silica powder, pulp sludge incineration ash, sewage sludge incineration ash, and waste glass powder. These volcanic ash substances are used alone or in combination.

[0058] As a preferred volcanic ash material used in combination with BFS, fly ash (hereinafter also referred to as "FA") can be exemplified. FA is fly ash generated when coal is burned in a coal-fired power plant, and is recovered from exhaust gas by a dust collector. The main components of FA are silicon dioxide, aluminum oxide, etc. FA is classified into types I to IV based on particle size and flow value in JIS A 6201. As preferred AF used in combination with BFS, types I and II, which have fine particle size and high reactivity, can be cited.

[0059] When BFS and an active filler other than BFS are used together, the amount of the active filler blended is not particularly limited and can be appropriately adjusted according to the intended use of the geopolymer hardened body and the desired mechanical properties such as compressive strength to be imparted to the geopolymer hardened body. When BFS and an active filler other than BFS are used together, the amount of the active filler blended is, for example, 10 to 200 parts by weight relative to 100 parts by weight of BFS. In another example, the amount of the active filler other than BFS blended is 100 to 200 parts by weight relative to 100 parts by weight of BFS. In addition, in another example, the amount of the active filler other than BFS blended is 10 to 100 parts by weight relative to 100 parts by weight of BFS.

[0060] 1-2. Active agent

[0061] The sodium silicate used as an active agent is sodium orthosilicate or anhydrous sodium metasilicate. Sodium silicate is also called water glass, and most of the compounds collectively referred to as water glass are in liquid form. For example, sodium silicate No. 1 to No. 3 specified in JIS K 1408 are all liquid. On the other hand, sodium metasilicate and sodium orthosilicate are in powder form. Sodium metasilicate is classified into three types: nonahydrate salt, pentahydrate salt and anhydrous salt according to the number of hydrated water molecules. The sodium metasilicate used in the active agent is an anhydrous salt among them. Sodium orthosilicate also has hydrated salts, but there is no classification based on the number of water molecules like sodium metasilicate. That is, the sodium orthosilicate used in the active agent can be an anhydrous salt or a hydrated salt.

[0062] Figure 1 : is a diagram showing the reaction formula of sodium orthosilicate and water. As can be seen from the reaction formula, sodium orthosilicate reacts with water to generate sodium metasilicate and sodium hydroxide. Therefore, if sodium orthosilicate is used as an active agent, the use of a high alkaline solution that is required in the past to obtain a hardened geopolymer can be omitted.

[0063] Figure 2 : is a diagram showing the reaction formula of anhydrous sodium metasilicate and water. As can be seen from the reaction formula, anhydrous sodium metasilicate reacts with water to generate a dimer of sodium silicate (water glass) and sodium hydroxide. Therefore, similar to orthosodium silicate, if anhydrous sodium metasilicate is used as an activator, the use of a high alkaline solution can be omitted.

[0064] When sodium orthosilicate is used as sodium silicate, the amount of sodium orthosilicate is 2 to 50 parts by weight relative to 100 parts by weight of the active filler. The lower limit of the amount is preferably 5 parts by weight, more preferably 15 parts by weight. On the other hand, the upper limit of the amount is preferably 45 parts by weight, more preferably 35 parts by weight.

[0065] When anhydrous sodium metasilicate is used as sodium silicate, the amount of anhydrous sodium metasilicate is 10 to 30 parts by weight relative to 100 parts by weight of the active filler. The lower limit of the amount is preferably 15 parts by weight. On the other hand, the upper limit of the amount is preferably 25 parts by weight.

[0066] The particle size of sodium orthosilicate and anhydrous sodium metasilicate is not particularly limited and can be appropriately adjusted according to the application of the geopolymer hardened body and the desired mechanical properties to be imparted to the geopolymer hardened body. As an example, the particle size is 1.2 mm or less. In another example, the particle size is 1.2 mm to 2.5 mm.

[0067] In the past, the pH of the highly alkaline solution required for obtaining the geopolymer hardened body was extremely high, being more than 13, and full attention was needed during the operation in the operation. In this regard, according to the geopolymer composition of the embodiment, the sodium hydroxide from sodium orthosilicate or anhydrous sodium metasilicate is generated by reaction with water. Therefore, the operational restrictions of the geopolymer composition can be reduced and the safety of the operation can be improved. In addition, sodium orthosilicate or anhydrous sodium metasilicate is in powder form, so it can be premixed and bagged with active fillers, and it also has the advantage of being able to suppress the occurrence of measurement errors at the operation site, etc.

[0068] 1-3. Other additives

[0069] The geopolymer composition of the embodiment may further contain various additives other than the above-mentioned active filler and active agent. Examples of the various additives include aggregates and setting regulators.

[0070] Aggregates are generally used to improve the material strength of concrete and mortar. Aggregates are classified into fine aggregates and coarse aggregates according to the size of the particles, natural aggregates and artificial aggregates according to the origin, and light aggregates, ordinary aggregates and heavy aggregates according to the density. The aggregates used in the geopolymer composition of the embodiment are not particularly limited and can be appropriately selected according to the purpose of the geopolymer hardened body and the desired mechanical properties to be given to the geopolymer hardened body.

[0071] As a preferred aggregate, fine aggregate can be mentioned, and as the fine aggregate, silica sand can be exemplified. Silica sand is a sand-like substance with silicon dioxide as a main component. As a preferred silica sand, JIS standard products and mixed silica sand with particle size adjusted according to JIS standards can be exemplified.

[0072] When adding aggregate, the amount thereof is not particularly limited and can be appropriately adjusted according to the purpose of the geopolymer hardened body and the desired mechanical properties to be imparted to the geopolymer hardened body. When adding aggregate, the amount of aggregate is, for example, 10 to 300 parts by weight relative to 100 parts by weight of BFS. In another example, the amount of aggregate is 150 to 300 parts by weight relative to 100 parts by weight of BFS. In another example, the amount of aggregate is 10 to 150 parts by weight relative to 100 parts by weight of BFS.

[0073] The setting agent is used to arbitrarily ensure the working time. Examples of the setting agent include citric acid, tartaric acid, gluconic acid, malic acid, or salts thereof, alkali metal carbonates, alkali metal hydrogen carbonates, and boric acid.

[0074] When a setting regulator is added, the amount thereof is 1 to 10 parts by weight relative to 100 parts by weight of the active filler. The upper limit of the amount is preferably 8 parts by weight, more preferably 5 parts by weight.

[0075] Various additives may further include fluidizers, thickeners (separation reducers) and rust inhibitors. Fluidizers are used to improve fluidity and filling properties without increasing the amount of water. As fluidizers, AE agents, AE water reducers, water reducers, high-performance water reducers and high-performance AE water reducers can be exemplified. Thickeners are used to suppress seepage when there is a lot of water or when the particle size of cement and aggregate is coarse. As thickeners, inorganic thickeners such as bentonite and organic thickeners such as cellulose or acrylic acid can be exemplified. Rust inhibitors are used to suppress corrosion of steel reinforcements used in temporary supports, advance supports, etc. As rust inhibitors, inorganic rust inhibitors such as nitrites, chromates, silicates, phosphates, organic rust inhibitors such as organic phosphates, organic acid esters, organic acids, sulfonic acids, amines, alkylphenols, thiols, nitro compounds, etc. can be exemplified.

[0076] 2. Geopolymer hardened body and its manufacturing method

[0077] The geopolymer hardened body of the embodiment comprises the geopolymer composition of the embodiment and water as a hardening agent. Figure 3 A method for producing the geopolymer cured body according to the embodiment will be described.

[0078] Figure 3 This is a flowchart showing an example of a method for producing a geopolymer cured body according to an embodiment. Figure 3 The example shown includes a kneading step S1 , a compression step S2 , a curing step S3 , and a drying step S4 .

[0079] The kneading step S1 is a step of mixing and kneading the geopolymer composition of the embodiment with water as a hardener. The amount of water added is appropriately adjusted according to the application of the geopolymer hardened body and the desired mechanical properties to be given to the geopolymer hardened body. In the kneading step S1, the geopolymer composition to which the above-mentioned various additives are added can be used according to the application of the geopolymer hardened body and the desired mechanical properties to be given to the geopolymer hardened body.

[0080] The compression step S2 is a step of molding and compressing the kneaded product obtained by the kneading step S1. In the compression step S2, a predetermined pressure (e.g., a pressure of 1 MPa or more) is applied to the kneaded product in order to stabilize the shape of the kneaded product and increase its density. Hereinafter, the kneaded product after the compression step S2 is also referred to as a "compressed kneaded product".

[0081] The curing step S3 is a step of curing the compressed kneaded product to allow the condensation reaction (hardening reaction) to proceed. The curing conditions are more than 3 hours at room temperature. The reason is that, as can be seen from the experimental examples described later, the geopolymer composition according to the embodiment can obtain the desired mechanical properties even under such conditions. In addition, the reason for making the curing time "more than 3 hours" is that the curing time required to obtain the desired mechanical properties is at least 3 hours. That is, the range of the curing time is not particularly limited, and it can be 3 hours to 4 hours, 3 hours to 6 hours, or 3 hours to 24 hours. Hereinafter, the compressed kneaded product that has undergone the curing step S3 is also referred to as a "cured kneaded product."

[0082] It should be noted that the kneaded product (i.e., the compressed kneaded product) after the compression step S2 and before being put into the curing step S3 is also considered to be a kneaded product in which the condensation reaction is not fully carried out, but there is also a kneaded product having desired mechanical properties. In this case, the compression step S2 and the curing step S3 are carried out in parallel, so the compression step S2 and the curing step S3 are not strictly distinguished.

[0083] The drying step S4 is a step of evaporating the water in the curing kneaded material. The curing kneaded material is dried naturally, but the drying can also be accelerated by adjusting the environmental conditions such as the temperature and humidity around the curing kneaded material. The curing kneaded material reaching a certain moisture content is equivalent to the geopolymer hardened body of the embodiment.

[0084] It should be noted that the moisture content of the kneaded product (i.e., the compressed kneaded product) before entering the curing step S3 sometimes reaches a certain moisture content. In this case, the compression step S2 and the drying step S4 are performed in parallel, so the compression step S2 and the drying step S4 are not strictly distinguished. In addition, the moisture content of the kneaded product (i.e., the cured kneaded product) after the curing step S3 sometimes reaches a certain moisture content. In this case, the curing step S3 and the drying step S4 are performed in parallel, so the curing step S3 and the drying step S4 are not strictly distinguished.

[0085] 3. Experimental Examples

[0086] Next, the embodiment will be described in detail with reference to experimental examples.

[0087] 3-1. Preparation of samples containing sodium orthosilicate

[0088] The samples of Examples 1 to 11 and Comparative Examples 1 to 8 having the various components shown in Table 1 at the blending ratios shown in Table 1 were prepared.

[0089] [Table 1]

[0090]

[0091] 3-2. Preparation of samples containing anhydrous sodium metasilicate

[0092] Samples of Examples 12 to 17 and samples of Comparative Examples 9 to 16 having the various components shown in Table 2 at the blending ratios shown in Table 2 were prepared.

[0093] [Table 2]

[0094]

[0095] BFS (blast furnace slag fine powder) "A" shown in Tables 1 and 2 is a sample with a Blaine surface area within the standard range (4160 cm 2 / g), blast furnace slag powder "B" is a sample with a Blaine surface area greater than the standard range (8470cm 2 / g). It should be noted that the Blaine specific surface area is a value measured in accordance with JIS R 5201 (physical testing methods for cement). In addition, the sodium orthosilicate "A" shown in Table 1 is a sample without adjusting the particle size, and the sodium orthosilicate "B" is a sample whose particle size is adjusted to 1.2 mm or less by classification.

[0096] 3-3. Evaluation of samples

[0097] The samples of the examples and comparative examples were kneaded to prepare hardened samples. Then, for each hardened sample prepared, (i) flow, (ii) setting time and (iii) compressive strength were measured. (i) Flow was measured according to the method described in "12. Flow test" of JIS R 5201. (ii) Setting time was measured according to the method described in "9. Setting test" of JIS R 5201. (iii) Compressive strength was measured according to the method described in "11. Strength test" of JIS R 5201.

[0098] Furthermore, the samples of the hardened bodies were evaluated based on the measurement results. Regarding (i) flowability, considering the workability as mortar, samples with a flow value of 140 mm or more after 15 drops were evaluated as "good". Regarding (ii) setting time, considering the workable time (usable time), samples with a flow value of 15 minutes or more were evaluated as "good". Regarding (iii) compressive strength, the compressive strength of the material after 3 hours of age was 3 N / mm 2 The above samples were evaluated as “good”. The evaluation results are shown in Tables 3 and 4.

[0099] [Table 3]

[0100]

[0101] From the results of "Flow" shown in Table 3, it can be seen that the flow values ​​of each sample of Examples 1-11 are good. In addition, from the results of "Setting Time", it can be seen that the setting time of each sample of Examples 1-3 and 5-9 is good. The setting time of each sample of Examples 4 and 10 is less than 15 minutes, but it is confirmed from the results of Example 11 that the setting time is extended by adding citric acid. Furthermore, from the results of "Compressive Strength", it can be seen that after curing for 3 hours in an atmosphere at 20°C (i.e., at room temperature), the compressive strength of each sample of Examples 1-11 is 3N / mm 2 above.

[0102] On the other hand, although the sample of Comparative Example 1 had a good flow value, it did not harden within 28 days. The reason for this is believed to be that the mixing ratio of sodium orthosilicate was too small. On the other hand, the samples of Comparative Examples 2 and 3 were samples with too much mixing ratio, and therefore, it was concluded that the flow value was low, the setting time was short, and the practicality was lacking.

[0103] The samples of Comparative Examples 4 to 8 are equivalent to the samples made according to the conventional method. The results of the flow value and the setting time of these samples are good (among them, the setting time of the sample of Comparative Example 7 in which the active filler is FA 100% is longer than that of the other samples). However, the results of the compressive strength are not good, and in order to obtain the desired compressive strength, 28 days of curing at room temperature are required, and 1 day of curing in 60°C steam (i.e., high temperature) is also required.

[0104] [Table 4]

[0105]

[0106] As shown in Table 4, the flow value of each sample of Examples 12 to 17 is good. In addition, as shown in the results of "setting time", the setting time of each sample of Examples 12 to 17 is good. Furthermore, as shown in the results of "compression strength", each sample of Examples 12 to 17 has a compression strength of 3 N / mm after curing for 3 hours in an atmosphere at 20°C (i.e., at room temperature). 2 above.

[0107] On the other hand, the sample of Comparative Example 9 was found to have a low flow value, a short setting time, and a lack of practicality. The reason for this is believed to be that the mixing ratio of anhydrous sodium metasilicate was too high. In this regard, the sample of Comparative Example 10 showed a good flow value, but did not harden within 28 days. The reason for this is believed to be that the mixing ratio of anhydrous sodium metasilicate was too low.

[0108] The samples of Comparative Examples 10-16 are equivalent to the samples made according to the conventional method. The flow value results of these samples are good. However, a setting time of more than 6 hours is required, and in order to obtain the desired compressive strength, curing at room temperature requires 1 day.

[0109] From such experimental results, it was confirmed that according to the embodiment, a highly practical geopolymer cured body having a desired compressive strength with a shorter setting time can be obtained. In addition, it was confirmed that the setting time can be extended by adding citric acid.

Claims

1. A geopolymer composition comprising: an active filler containing at least blast furnace slag powder; and sodium silicate as an active agent, The geopolymer composition is characterized in that The sodium silicate is orthosodium silicate or anhydrous sodium metasilicate. When the sodium silicate is orthosilicate, the content of the orthosilicate is 2 parts by weight to 50 parts by weight relative to 100 parts by weight of the active filler. When the sodium silicate is anhydrous sodium metasilicate, the content of the anhydrous sodium metasilicate is 10 parts by weight to 30 parts by weight based on 100 parts by weight of the active filler.

2. The geopolymer composition according to claim 1, wherein: The lower limit of the content of the sodium orthosilicate is 5 parts by weight.

3. The geopolymer composition according to claim 1 or 2, wherein: The upper limit of the content of the sodium orthosilicate is 45 parts by weight.

4. The geopolymer composition according to claim 1, wherein: The lower limit of the content of the anhydrous sodium metasilicate is 15 parts by weight.

5. The geopolymer composition according to claim 1 or 2, wherein: The upper limit of the content of the anhydrous sodium metasilicate is 25 parts by weight.

6. The geopolymer composition according to any one of claims 1 to 5, wherein The blast furnace slag powder contains a Blaine specific surface area in the range of 3000cm 2 / g~4000cm 2 The standard surface area of ​​powder and Blaine surface area range is 6000cm / g 2 / g~10000cm 2 / g of high surface area powder.

7. The geopolymer composition according to any one of claims 1 to 6, wherein The active filler also includes pozzolanic material.

8. A geopolymer hardened body, comprising: an active filler containing at least blast furnace slag powder; sodium silicate as an active agent; and water as a hardening agent, The geopolymer hardened body is characterized in that: The sodium silicate is orthosodium silicate or anhydrous sodium metasilicate. When the sodium silicate is orthosilicate, the content of the orthosilicate is 2 parts by weight to 50 parts by weight relative to 100 parts by weight of the active filler. When the sodium silicate is anhydrous sodium metasilicate, the content of the anhydrous sodium metasilicate is 10 parts by weight to 30 parts by weight based on 100 parts by weight of the active filler.

9. A method for producing a geopolymer hardened body, characterized in that: include: A process of adding water to a geopolymer composition and kneading the geopolymer composition, wherein the geopolymer composition comprises an active filler containing at least blast furnace slag powder and sodium silicate as an active agent; and The kneaded product obtained by the kneading step is cured at room temperature for 3 hours or more, The sodium silicate is orthosodium silicate or anhydrous sodium metasilicate. When the sodium silicate is orthosilicate, the content of the orthosilicate is 2 parts by weight to 50 parts by weight relative to 100 parts by weight of the active filler. When the sodium silicate is anhydrous sodium metasilicate, the content of the anhydrous sodium metasilicate is 10 parts by weight to 30 parts by weight based on 100 parts by weight of the active filler.